2010
DOI: 10.1002/tal.673
|View full text |Cite
|
Sign up to set email alerts
|

Accelerographic measurements of the 27 February 2010 offshore Maule, Chile earthquake

Abstract: The mega earthquake of 27 February 2010, offshore Maule, Chile with moment magnitude of 8·8 is the fi fth largest recorded earthquake in the world and, therefore, is considered to be a mega earthquake. This subduction interplate thrust earthquake occurred at the convergence of the Nazca (oceanic) plate with the South American continental plate. This type of earthquake affects the north-western region of USA and Canada, as well as Alaska. Therefore, it is important to study the characteristics of the recorded a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Box 9140, Boulder, CO 80301, USA. ing the last 2010 M w 8.8 Maule megathrust rupture (Saragoni et al, 2010). However, all those values should be considered as lower estimates because they do not incorporate possible effects of basin topography or earthquake directivity.…”
Section: Earthquake Estimates and Implications For Seismic Hazardmentioning
confidence: 99%
“…Box 9140, Boulder, CO 80301, USA. ing the last 2010 M w 8.8 Maule megathrust rupture (Saragoni et al, 2010). However, all those values should be considered as lower estimates because they do not incorporate possible effects of basin topography or earthquake directivity.…”
Section: Earthquake Estimates and Implications For Seismic Hazardmentioning
confidence: 99%
“…Near‐fault ground motion records may contain high amplitude acceleration, velocity, and displacement pulses . High amplitude low frequency pulses are contained in far field ground motions affected mostly by site effects . The waveform, predominant period, and amplitude of the pulses determine the motion's damage potential for different structures .…”
Section: Near‐fault Ground Motions and Their Closed‐form Representationmentioning
confidence: 99%
“…">NEAR-FAULT GROUND MOTIONS AND THEIR CLOSED-FORM REPRESENTATIONNear-fault ground motion records may contain high amplitude acceleration, velocity, and displacement pulses [35]. High amplitude low frequency pulses are contained in far field ground motions affected mostly by site effects [36,37]. The waveform, predominant period, and amplitude of the pulses 1302 V. CALUGARU AND M. PANAGIOTOU Figure 10.…”
mentioning
confidence: 99%
“…The 27 February 2010 Maule (Chile) earthquake suggested that the proximity to fault asperities can control structural failures, because the most damaged cities in Chile were close to two identified asperities [12]. The 11 March 2011 Tohoku (Japan) earthquake has reinforced the idea that strong effects due to local asperities, cause significant variability of ground motion parameters at short rupture distances and similar site conditions [13].…”
Section: Earthquake Source Characteristicsmentioning
confidence: 99%